Предмет: Математика,
автор: ЗаНоЗа012002
упростите выражение и найдите его значения x(x-3)(4-x)=16-x(x-3.5)^2
Ответы
Автор ответа:
0
x*(x-3)*(4-x) = 16-x*(x-(7/2))^2
-x^3 - 12*x + 7*x^2 = 16-x*(x-(7/2))^2
-x^3 - 12*x + 7*x^2 = 16 - x^3 + 7*x^2 - 49*x/4
-16 + x/4 = 0
x/4 = 16
x = 16 / (1/4)
x = 64
-x^3 - 12*x + 7*x^2 = 16-x*(x-(7/2))^2
-x^3 - 12*x + 7*x^2 = 16 - x^3 + 7*x^2 - 49*x/4
-16 + x/4 = 0
x/4 = 16
x = 16 / (1/4)
x = 64
Похожие вопросы
Предмет: Математика,
автор: medetkerimbaev86
Предмет: Математика,
автор: QW3R1Y
Предмет: Русский язык,
автор: Gameover761771627272
Предмет: Математика,
автор: б1б